On making, tinkering, coding and play for learning: A review of current research - Timotheou, Stella; Ioannou, Andri (My University, 2019)
Although a few researchers have recently focused on the value of making, tinkering, coding, and play in learning, a synthesis of this work is currently missing, creating an unclear path for future research in this area. Computational-making-enhanced activities, framed as activities promoting making, tinkering, coding and play in the learning process, have gained a lot of attention during the last decade. This study provides a review of the existing research in this area, published in academic journals, from 2009 to 2018. We examine learning gains linked to learners’ participation in computational making-enhanced activities in formal and non-formal education settings. We further overview the research methods, the educational level, and the context of the published studies. The review of selected studies has shown that most of the research has been conducted in non-formal and informal education settings, however a shift to formal education has appeared since 2016. Most studies have focused on programming and computer science with middle-school learners. Immediate action is needed to inform the design of computational-making-enhanced activities directly linked to curriculum goals. Given the lack of synthesis of work on computational-making, the review can have considerable value for researchers and practitioners in the field.
Keywords: Coding; Computational making; Play; Technology-enhanced learning; Tinkering